Pd(0)-Sb@A@SiO2@NiFe2O4 yolk-shell nanostructures as an effective and reusable nanocatalyst for the synthesis of symmetrical sulfides and unsymmetrical ethers - Anjan Kumar; Ahmed M. Naglah; Chou-Yi Hsu; Jayanti Makasana; Suhas Ballal; Munther Kadheem; Abhayveer Singh; T. Krithiga; Swati Mishra; Pushpa Negi Bhakuni (Scientific Reports)
Abstract A highly efficient magnetic nanocatalyst has been developed by covalently grafting a Pd(0)-Sb@A complex onto a silica-coated nickel ferrite support. This innovative nanocatalyst has been thoroughly analyzed using various techniques, including FT-IR, VSM, XRD, ICP, EDX, XPS, TEM, and FE-SEM. Its performance was then evaluated in the synthesis of symmetrical sulfides and unsymmetrical ether derivatives. Key advantages of this approach include high product yields, reduced reaction times, straightforward synthesis, easy magnetic separation, and excellent catalyst recoverability, maintaining activity for at least four cycles without notable degradation.